Physiological demands of simulated off-road cycling competition - Smekal, G.; von Duvillard, S. P.; Hörmandinger, M.; Moll, R.; Pokan, R. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Only limited empirical evidence is available to assess the physiology of competitive off-road cycling (COMP). Earlier studies investigating energetic demands of mountain bike (MB)-cycling were often based on heart rate (HR) and blood lactate (BLa) measures. Only few papers are available dealing with power output (PO)-and respiratory gas measures during COMP. However, the workloadpattern of COMP limits the utility of HR and BLa measures since BLa is slowly removed from blood and rather may reflect high intensity periods while HR has been shown to be influenced by psychological components. PO measures represent exertion of force expended by lower limbs and not overall physical demands of COMP requiring recruitment of additional muscle mass stabilizing against gravity and vibration. Considering these limitations the aim of our study was to describe COMPs via the combination of BLa measures and real-time measures of PO, HR and respiratory gas parameters. Methods: 24 male competitive cyclists performed our COMP and also laboratory tests (LabT). From LabT study parameters data were determined at maximal load and 2 ventilatory thresholds (VT1, VT2). A highperformance athlete (HPA) was used to demonstrate COMP on high level. The COMP-trail was a rocky, hilly single trail with many roots and stones (four identical laps, entire distance of ~24.348 km). Results: During the COMP, athletes achieved a mean oxygen uptake (VO2COMP) of 57.0±6.8 ml/kg/min vs.71.1 ml/kg/min for the HPA. The POCOMP was 2.66±0.43 W/kg and 3.52 W.kg-1 for the HPA. We further analyzed POCOMP, VO2COMP, HRCOMP in relation to corresponding variables of LabTs. Mean POCOMP was 61.9% of POVT2 and 47.2% of POmax, whereas VO2COMP was 112 % of VO2VT2 and 88 % of VO2peak and HRCOMP was 102 % of HRVT2 and 90% of HRmax. POCOMP, VO2COMP and HRCOMP were compared to corresponding variables at the VT2 of LabT. LabT variables correlated with racing time (RTCOMP) and POCOMP (P<0.01 to<0.001; r-0.59 to -0.80). Discussion/ Conclusion: The study resulted in following findings: During COMP high oxygen costs exist probably influenced by the high muscle mass simultaneously working. POCOMP turned out to be lower when compared to VO2COMP , likely caused by phases of low force production (downhill phases) and also by the high mass performing COMP at this selective MB-trail. Data determined from LabT might be utilized to describe semi-specific abilities of MB- athletes and cannot be transferred to MB-cycling. Data originating from COMPs might be useful when designing MB-specific training.